Weed management and its influence on the load bearing capacity of red-yellow latosol under the crown projection, in coffee culture - Santos, Gislene Aparecida dos; Dias Junior, Moacir de Souza; Guimarães, Paulo Tácito Gontijo; Araújo Junior, Cezar Francisco; Sant’Anna Moreira, Paula Sant’Anna (Coffee Science - ISSN 1984-3909, 1970)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} h1 {mso-style-unhide:no; mso-style-qformat:yes; mso-style-link:"Título 1 Char"; mso-style-next:Normal; margin:0cm; margin-bottom:.0001pt; line-height:150%; mso-pagination:widow-orphan; page-break-after:avoid; mso-outline-level:1; font-size:11.0pt; mso-bidi-font-size:12.0pt; font-family:"Times New Roman","serif"; mso-font-kerning:0pt;} span.Ttulo1Char {mso-style-name:"Título 1 Char"; mso-style-unhide:no; mso-style-locked:yes; mso-style-link:"Título 1"; mso-ansi-font-size:11.0pt; mso-bidi-font-size:12.0pt; font-weight:bold;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif]--> Weed management is identified as a major cause of soil compaction in coffee plantations, because of its necessary frequent undertaking. The objectives of this study were: a) to develop bearing capacity models, for a Red-Yellow Latosol cultivated with coffee (Coffea arabica, L.), as a function of the associated weed management methods, preconsolidation pressure and moisture; b) to identify, through the use of these models, the weed management more resistant and more susceptible to soil compaction, under the coffee crown projection. This study was carried out in an experiment installed in the Experimental Farm of EPAMIG in Patrocínio MG, using the Rubi cultivar 1192. The weed control methods were: Hand hoe, Post-emergence herbicide, Pre-emergence herbicide and Brush Trimmer (Roçacarpa – commercial name), associated with the rotary tiller, disk harrow, were mower and no weed control between plant rows. For each weed management, 15 samples were collected at depths of 0-3, 10-13 and 25-28 cm, to generate the capacity bearing model, totaling 720 undisturbed soil samples. To obtain the capacity bearing models, the undisturbed soil samples with different moisture content were submitted to the uniaxial compression tests according to Bowles (1986) modified by Dias Junior (1994). The pre-emergence herbicide associated to no weed control condition and were mower and the hand hoe associated to no weed control presented higher resistance to soil compaction. The Brush Trimmer (Roçacarpa) methods, associated to were mower; the Pre-emergence herbicide, associated to rotary tillers; and Pre-emergence herbicide and Brush Trimmer, associated to disk harrow between rows, presented higher susceptibility to soil compaction.